Estimation of Population Size and Dispersal Pattern of Sterile Male Aedes aegypti Using Mark-Release-Recapture (MRR) Technique - R. Zulfa; S. Yuliawati; M. Martini; R. Hestiningsih; B. Ernawan (Atom Indonesia, 2021)
Aedes aegypti is currently emerging as a main vector of Dengue, Zika, and Chikungunya transmission. Chemical control was reported to be less effective due to the resistance of this mosquito to some types of insecticides. Therefore, another vector control is needed which is most appropriate to be used, i.e. the sterile insect technique (SIT). Information about optimum range dispersal sterile male Aedes aegypti for optimalization SIT program are needed. This study was designed to determine the dispersal pattern and population estimation of Aedes aegypti sterilized with gamma rays using mark-release-recapture (MRR) method. After the male Aedes aegypti (pupal stage) was irradiated with 70 Gy of gamma rays, the mosquitoes were then marked with Rhodamine-B and released into the study site. MRR experiments were carried out in Batan Indah residential area, and the Aedes aegypti were released in center of the site. Mosquitoes were recaptured at 28 points spread over the Batan Indah Residence for 2, 4, 6, and 8 days after release by using BG-Sentinel Traps. The result showed that the population of Aedes aegypti in the site was estimated to be 5.402 (1.347–14.636; CI 95 %) with the furthest spread distance was 119 meters from the release point. This study also showed that the MRR experiment can be used to estimate the population size and dispersal pattern of Aedes aegypti movement in a given locality. The result of present study provide better understanding for optimalization mosquito-borne disease prevention based on SIT programs.